Karakteristik Analisis LCS Meningoensefalitis Anak di RSUD Abdoel Wahab Sjahranie Samarinda Tahun 2019-2022 - Yunita Yunita; Yudanti Riastiti; Annisa Muhyi (Fakultas Kedokteran, Universitas Andalas, 2023)
Meningoencephalitis is a pathological state characterized by concurrent inflammation of the meninges and the brain parenchyma. Liquor Cerebrospinal analysis (LCS) can help establish a diagnosis of diseases affecting the central nervous system, including meningoencephalitis. Objective: To identified the attributes of meningoencephalitis LCS analysis in pediatric patients at RSUD Abdoel Wahab Sjahranie Samarinda from 2019 until 2022. Methods: This study employs a descriptive research design to delineate the features of the LCS analysis. The data utilized in this study was acquired from the medical records of individuals who had experienced meningoencephalitis during their childhood and obtained as many as 39 patient data samples. Results: The findings revealed that most cases were observed in children aged 0-1 years (38.5%), with a higher incidence in males (59.0%). The LCS analysis parameters indicated that lymphocytic pleocytosis was the most common (76.9%), while clear LCS was observed in 82.1%. The leukocyte count was within the normal range of 56.4%, and the polymorphonuclear ratio was negative (79.5%). The protein levels increased by 56.4%, while the glucose levels were within the normal range (59.0%). Conclusion: There is an increase in LCS protein levels, which indicates inflammation.Keywords: LCS analysis, LCS parameters, meningoencephalitis